2014
DOI: 10.1186/1471-2393-14-160
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of maternal and neonatal outcomes between water immersion during labor and conventional labor and delivery

Abstract: Background: Water immersion during the first stage of labor can reduce the length of the first stage and epidural/ spinal analgesia use; however, there is limited information regarding other outcomes. Our purpose was to compare maternal and neonatal outcomes of women who underwent water immersion during the first stage of labor with those who underwent conventional labor and delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
58
2
18

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(83 citation statements)
references
References 18 publications
5
58
2
18
Order By: Relevance
“…The researchers also found that hydrotherapy was associated with a higher chance of vaginal birth (RR 1.09; 95% CI 1.04-1.15) and an overall reduction in birthing interventions in freestanding midwifery clinics (RR 0.61, 95% CI 0.48-0.77) (Lukasse et al, 2014). Liu et al (2014) conducted a case-control study of women in labour (n=108) in China. Thirty-eight participants received water immersion and 70 received standard care but did not opt for hydrotherapy.…”
Section: Safety and Benefits Of Hydrotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…The researchers also found that hydrotherapy was associated with a higher chance of vaginal birth (RR 1.09; 95% CI 1.04-1.15) and an overall reduction in birthing interventions in freestanding midwifery clinics (RR 0.61, 95% CI 0.48-0.77) (Lukasse et al, 2014). Liu et al (2014) conducted a case-control study of women in labour (n=108) in China. Thirty-eight participants received water immersion and 70 received standard care but did not opt for hydrotherapy.…”
Section: Safety and Benefits Of Hydrotherapymentioning
confidence: 99%
“…Water immersion does not appear to increase the rate of maternal or neonatal infections and is associated with a lower rate of stress urinary incontinence 42 days postpartum (p=0.03), a variable not mentioned in earlier studies. (Liu et al, 2014) A randomized control trial studying the efficacy of hydrotherapy took place in Taipei in a study conducted by Lee, Liu, Lu, and Gau (2013). The study examined the effect of 20-minute warm showers on parturients (n=39) able to control the direction of water flow at a controlled temperature during the first active phase of labour (control group [n=41] received standard care).…”
Section: Safety and Benefits Of Hydrotherapymentioning
confidence: 99%
“…Water preparation may also lower cesarean delivery rate and problems post-delivery. Water immersion during labor could not find increasing infections in both the mother and the neonate [6]. A joint statement issued by the British Royal College of Obstetricians and Gynaecologists and the Royal College of Midwives supports water birth for normal and healthy women with easy and unproblematic pregnancies.…”
mentioning
confidence: 96%
“…Reproductive failures, metritis, mastitis, and deficient immune function are amongst the most significant consequences of dystocia or calving difficulty in dairy cows, for instance. Thus, water birth or underwater preparation for parturition comes to play a critical role in minimizing parturition challenges and pains.Water birth has been a matter of debate in human physiology and medicine [4][5][6][7][8][9][10]. Despite the potential benefits and risks, the concept has not been scientifically matured and globalized towards practical applications and specialized guidelines.…”
mentioning
confidence: 99%
See 1 more Smart Citation